Reply to my Critics: Justifying the Fair Share Argument. Issue 2 (3rd May 2016) - Baatz, Christian
Abstract: In an earlier article I argued that individuals are obligated not to exceed their fair share of emissions entitlements, that many exceed their fair share at present and thus ought to reduce their emissions as far as can reasonably be demanded. The peer commentators raised various insightful and pressing concerns, but the following objections seem particularly important: It was argued that the fair share argument is insufficiently justified, that it is incoherent, that it would result in more far-reaching duties than acknowledged by me, that it is unable to provide a clear account of individual duties, and that duties to reduce individual emissions are not Kantian imperfect duties. This reply aims at clarifying the fair share argument and at addressing the major challenges.